Kinetics and Mechanism of the Thermal Decomposition of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) Complexes of Vanillin-2-aminopyridne - Sleema, B.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
The thermal decomposition of Mn(II), Co(II), Ni(II), Cu(II) and Zn(II) chelates of vanillin-2-amino pyridine was studied by TG. The mechanism of the decomposition has been established from TG data. The kinetic parameters, viz., activation enetgy E, pre-exponential factor A and order of reaction n, were calculated from the TG curves using mechanistic and non-mechanistic (Coats-Redfern) integral equations.